Participation of ionic forms in bisphenol phototransformation under sunlight exposure - Bazyl, Olga K.; Bocharnikova, Elena N.; Tchaikovskaya, Olga N.; Mayer, Georgy V. 1948- (Russian physics journal)
The absorption and fluorescence spectra of charged anionic and cationic forms of bisphenol A (BPA) have been studied. The nature of electronically excited states and the photolysis of the BPA molecule have been interpreted based on results of quantum chemical calculations. The BPA spectra in an aqueous solution are compared during transition from the neutral to the ionic form. Results of calculations have shown that the small value of the fluorescence quantum yield in all examined molecular structures is determined by the high efficiency of the singlet-triplet conversion. In the anionic BPA form, a decrease in the efficiency of radiation decay channel by two orders of magnitude has been recorded caused by a change in the orbital nature of the fluorescent state compared to the neutral and cationic forms. It is shown that the probability of photolysis of the molecule under study increases due to the overlap of the absorption spectra of the anionic form in an aqueous solution under exposure to sunlight.